2004
DOI: 10.17221/4049-pse
|View full text |Cite
|
Sign up to set email alerts
|

Yield and forage quality of red clover (Trifolium pratense L.) cultivars in the lowland and the mountain regions

Abstract: Six Trifolium pratense L. cultivars, five diploid and one tetraploid, were grown in the lowland region (123 m altitude) and the mountain region (650 m altitude). Dry ma�er (d.m.) and green mass (g.m.) yield, stem height and leaf proportion were assessed from each of the three growing seasons. Chemical composition was assessed from the average samples of all cuts in the second year of the experiment. Greater green mass (54.14 t/ha) and dry ma�er yield (9.86 t/ha), stem height (0.61 m), crude protein (157.6 g/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 2 publications
2
14
0
Order By: Relevance
“…This was especially evidentc for tetraploids due to their higher content of water. Some investigations have shown that forage yield of tetraploid can be higher more than 50% in cases when DM yield is higher only by up to 10% (Leto et al, 2004;Zuk-Golaszewska et al, 2010). Our results confirm this relationship, as forage yield of tetraploid genotypes was higher by 12.3%, compared that of with diploid genotypes, while DM yield was higher by only by 6.5%.…”
Section: Discussionsupporting
confidence: 89%
“…This was especially evidentc for tetraploids due to their higher content of water. Some investigations have shown that forage yield of tetraploid can be higher more than 50% in cases when DM yield is higher only by up to 10% (Leto et al, 2004;Zuk-Golaszewska et al, 2010). Our results confirm this relationship, as forage yield of tetraploid genotypes was higher by 12.3%, compared that of with diploid genotypes, while DM yield was higher by only by 6.5%.…”
Section: Discussionsupporting
confidence: 89%
“…The usual stand life for red clover production is no longer than three years, with few cuts and in one growing. Under ecological conditions of West Croatia had achieved average annual forage yield from 9.18 to 10.8 t ha -1 (Leto et al, 2004). It is a perennial, diploid (2n = 2x = 14) and outcrossing species with a gametophytic selfincompatibility system (Taylor, Quesenberry, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the tetraploid germplasm in summer drought, typical for the plains of Northern Bulgaria, stops growing and does not compensate for its limited vegetative growth, despite the excellent moisture guarantee in the late summer, as well as in the spring the next growing season. The conclusion about reduced productivity and persistence of tetraploids on dry conditions or uneven distribution of rainfall during vegetation is also supported by Leto et al (2004). (Loucks, 2017).…”
Section: Discussionmentioning
confidence: 81%